Associations between lower limb eccentric muscle capability and change of direction speed in basketball and tennis players - Smajla, Darjan; Kozinc, Žiga; Šarabon, Nejc (PeerJ, 2022)
Background The ability to perform a quick and rapid change of direction (CoD) is an important determinant of success in a variety of sports. Previous studies have already highlighted that eccentric strength is a dominant predictor of CoD. However, these studies evaluated eccentric strength through a limited number of outcome measures and used small sample sizes. Methods A total of 196 athletes participated in the study. The aim of our study was to investigate: (1) the correlation between eccentric outcome measures derived from different tests (Nordic hamstring exercise (NHE), countermovement jump (CMJ) and flywheel (FW) squats), (2) the association between eccentric outcome measures and CoD 90°, CoD 180°; and (3) proportion of explained variance in CoD performance. Results Very large associations (r = 0.783, p < 0.001) were observed between peak torque during NHE (NHEPT) and force impulse during the eccentric phase of CMJ (CMJFI). Small to moderate correlations were calculated between peak eccentric force in flywheel squats and peak eccentric force in CMJ (r = 0.220–035, p < 0002). All eccentric CMJ outcome measures and NHEPT were reported as moderate negative associations with both CoD tests. Eccentric measures explained 25.1% of the variance in CoD 90° (CMJPF, NHEPT, F0.125 –peak eccentric force during FW squats with 0.125 kg m2 load), while the same outcome measures explained 37.4% of the variance for CoD 180°. Conclusion Our results suggest that different measures of eccentric strength specifically contribute to CoD performance. Therefore, for successful CoD performance, different aspects of eccentric strength training should be considered in testing and training (maximal eccentric strength, eccentric-concentric actions with fast execution).
Keywords: Deceleration; Braking; Strength; Power; Agility